Dampak Kelebihan Jam Kerja Pada Personil PKP-PK Bandar Udara Internasional Juanda - Krisna Adiguna, Nicomedes; Ramadhan, Ryan; Sadiq Arjuna, Imam; Mohammad Fadillah, Ilham; Rini; Hendra, Oke (Politeknik Penerbangan Makassar, 2021)
This study aims to determine the impact that can be caused by excessive working hours. The method used in conducting this research is qualitative. The data is obtained by going directly to the field and participating directly in all activities (participant observation). Furthermore, this data is adjusted to the existing regulations, namely the Manpower Law No. 13 of 2003. Then it was found that there were excess working hours charged to ARFF (Airport Rescue and Fire Fighting) personnel which could trigger dangerous events in the future. After this research was conducted, a solution was obtained to provide KJK (Excess Working Hours) by existing regulations, changing shift schedules, and adding entertainment or sports facilities.